The Difference of Soil Transmitted Helminths (STH) on Vegetables in Traditional and Modern Markets - Rahmadani Sitepu (Indonesian Journal of Education and Mathematical Science, 2020)
Soil Transmitted Helmiths (STH) infections is still a problem in many areas of the world, there are more than 1.5 billion people, or 2.4% of the world population is infected with intestinal worms that are transmitted through the soil. STH distribution in Indonesia includes all islands in Indonesia, where the prevalence is highest in Papua and North Sumatra with a prevalence of between 50% to 80%. One source of infection was water and mud used in the cultivation of vegetables. Contamination worms may occur especially on vegetables that propagate in the soil or close to the soil. This research is performed in an analytic study with cross sectional design. vegetables are included in the sample in this research was lettuce, leeks, cabbage, spinach, and mustard as many as 50 samples taken from traditional markets and modern markets in Medan city. From the results done, it is known that the highest positive results is in traditional markets as much as 10 vegetables or (40.0%) and the lowest positive results is in modern markets as much as 3 vegetables or (25.0%). Based on these results we can conclude that there are differences between traditional markets and modern markets as evidenced by the value of p in this comparison are p=0,035, So there are differences of Soil Transmitted helminths contamination in raw vegetables sold in traditional markets and modern markets